Carbon Capture and Storage: History and the Road Ahead. (July 2022) - Ma, Jinfeng; Li, Lin; Wang, Haofan; Du, Yi; Ma, Junjie; Zhang, Xiaoli; Wang, Zhenliang
Abstract: The large-scale deployment of carbon capture and storage (CCS) is becoming increasingly urgent in the global path toward net zero emissions; however, global CCS deployment is significantly lagging behind its expected contribution to greenhouse gas emission reduction. Reviewing and learning from the examples and history of successful CCS practices in advanced countries will help other countries, including China, to promote and deploy CCS projects using scientific methods. This paper shows that the establishment of major science and technology CCS infrastructures in advanced countries has become the main source of CCS technological innovation, cost reduction, risk reduction, commercial promotion, and talent training in the development and demonstration of key CCS technologies. Sound development of CCS requires a transition from pilot-scale science and technology infrastructures to large-scale commercial infrastructures, in addition to incentive policies; otherwise, it will be difficult to overcome the technical barriers between small-scale demonstrations and the implementation of million-tonne-scale CCS and ten-million-tonne-scale CCS hubs. Geological CO2 storage is the ultimate goal of CCS projects and the driving force of CO2 capture. Further improving the accuracy of technologies for the measurement, monitoring, and verification (MMV) of CO2 storage capacity, emission reduction, and safety remains a problem for geological storage. CO2 storage in saline aquifers can better couple multiple carbon emission sources and is currently a priority direction for development. Reducing the energy consumption of low-concentration CO2 capture and the depletion of chemical absorbents and improving the operational efficiency and stability of post-combustion CO2 capture systems have become the key constraints to large-scale CCS deployment. Enhanced oil recovery (EOR) is also important in order for countries to maximize fossil fuel extraction instead of importing oil from less environmentally friendly oil-producing countries.